2017
DOI: 10.1002/jbm.a.36286
|View full text |Cite
|
Sign up to set email alerts
|

The effect of temporal manipulation of transforming growth factor beta 3 and fibroblast growth factor 2 on the derivation of proliferative chondrocytes from mensenchymal stem cells—A study monitored by quantitative reverse transcription polymerase chain reaction and molecular beacon based nanosensors

Abstract: Proliferative chondrocytes are critical to realize regeneration of damaged epiphyseal growth plate. However, acquiring autologous replacement cells involves highly invasive procedures and often results in limited cell quantity. Mesenchymal stem cells (MSCs) are a potential source of chondrogenic cells for the treatment of cartilage disorders and injuries. The temporal effect of transforming growth factor beta 3 (TGFβ3) and fibroblast growth factor 2 (FGF2) on the derivation of proliferative chondrocytes from M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…For chondrocyte taxonomy, some studies have shown chondrocyte subtypes mainly included ProCs, preHTCs and HTCs [29][30][31]. In addition to these three common chondrocyte subtypes, QB and his partners rst identi ed 4 new populations of chondrocytes in the human OA cartilage by performing unbiased transcriptome-wide scRNA-seq analysis and computational analysis on some chondrocytes from 10 OA patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…For chondrocyte taxonomy, some studies have shown chondrocyte subtypes mainly included ProCs, preHTCs and HTCs [29][30][31]. In addition to these three common chondrocyte subtypes, QB and his partners rst identi ed 4 new populations of chondrocytes in the human OA cartilage by performing unbiased transcriptome-wide scRNA-seq analysis and computational analysis on some chondrocytes from 10 OA patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…For chondrocyte taxonomy, some studies have shown chondrocyte subtypes mainly included ProCs, preHTCs and HTCs [29][30][31]. In addition to these three common chondrocyte subtypes, Ji et al rst identi ed 4 new populations of chondrocytes in the human OA cartilage by performing unbiased transcriptome-wide scRNA-seq analysis and computational analysis on some chondrocytes from 10 OA patients [16].…”
Section: Discussionmentioning
confidence: 99%
“…The concurrent application of hypoxia and FGF-2 could provide a favorable condition for culturing human bone marrow-derived stem cells to be used in clinical applications associated with bone tissue engineering, due to the enhancement of cellular proliferation and regenerative potential (24). The effects of temporal manipulation were achieved by applying FGF-2 and transforming growth factor-β3 on the derivation of proliferative chondrocytes from mesenchymal stem cells (25).…”
Section: Discussionmentioning
confidence: 99%